Plan de negocios para la creación de una empresa dedicada al diseño, elaboración y comercialización de camisetas estampadas enfocadas en la música electrónica - Mantilla Sarmiento, Esperanza Catalina (2010)
This business plan is focused toward creating TTex Co. Ltd., a company which manufactures and markets Nirvage-branded T-shirts for a youth market that enjoys listening to electronic music. This idea came about due to (1) the impact this kind of music has had on the local market (Quito), (2) the increase in young listeners, and (3) the lack of products tailored for this niche, which is why evaluating its business feasibility and practicality is of utter importance. Consequently, in order to carry out this task, it has been necessary to conduct a study of macro- and micro-market environments, which have helped to identify the main opportunities and threats affecting the business implementation, and which have impacted the setting of market and product strategies coming from the highly specialized strategy. The products to be marketed are printed T-shirts with original designs that relate to this type of music. It uses shapes and colors that will differ from those in the market due to the product’s quality and differentiating concept. This is reinforced by the positioning and branding strategies detailed in the Marketing Plan chapter. Defining the type of culture and structure that the company should have in order to operate efficiently has also been taken into account as an essential part of the Business Plan. Finally, we have determined that the total necessary investment would be 121,541.32 dollars, of which 86% accounts for working capital. This would be used to cover costs and expenses for a semester, which shows that the fixed investment is low and that the marketing effort is one of the most representative ones we have. According to the financial assessment of scenarios, we can see that we are dealing with a profitable business, including a positive NPV in all cases and an IRR higher than the project is opportunity cost.